2020
DOI: 10.7717/peerj.9309
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome of the nonphotosynthetic mycoheterotrophic plant Hypopitys monotropa, its structure, gene expression and RNA editing

Abstract: Heterotrophic plants—plants that have lost the ability to photosynthesize—are characterized by a number of changes at all levels of organization. Heterotrophic plants are divided into two large categories—parasitic and mycoheterotrophic (MHT). The question of to what extent such changes are similar in these two categories is still open. The plastid genomes of nonphotosynthetic plants are well characterized, and they exhibit similar patterns of reduction in the two groups. In contrast, little is known about the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…The RNA read depth of each of the 33 protein-coding genes is consistent across the three samples (Table S1). In agreement with previous studies in Arabidopsis [20] and other plants [35], atp9 shows the highest read depth (RPKM = 361,785-369,149), while ccmFn1 (RPKM = 529-638) followed by ccmFn2 (RPKM = 998-1421), rps7 (RPKM = 3911-3580) and rps4 (RPKM = 4576-4635) show the lowest read depth across the three samples. The two copies of atp6 show different RNA read depth, with that of atp6-1 being consistently greater than that of atp6-2 in the three data sets.…”
Section: Protein-coding Genes Show Elevated Rna Read Depthsupporting
confidence: 92%
See 1 more Smart Citation
“…The RNA read depth of each of the 33 protein-coding genes is consistent across the three samples (Table S1). In agreement with previous studies in Arabidopsis [20] and other plants [35], atp9 shows the highest read depth (RPKM = 361,785-369,149), while ccmFn1 (RPKM = 529-638) followed by ccmFn2 (RPKM = 998-1421), rps7 (RPKM = 3911-3580) and rps4 (RPKM = 4576-4635) show the lowest read depth across the three samples. The two copies of atp6 show different RNA read depth, with that of atp6-1 being consistently greater than that of atp6-2 in the three data sets.…”
Section: Protein-coding Genes Show Elevated Rna Read Depthsupporting
confidence: 92%
“…Occasionally, non-coding regions show high RNA read depth suggesting a possible role as long non-coding RNAs. These regions are generally not conserved and have not been further characterized [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The base composition of the final assembly version is A = 27.16%, C = 22.78%, G = 22.84%, T = 26.99%, and consists of 23 transfer RNAs and 33 protein coding genes (12 of them partial). In comparison to mitochondrial genomes from other members of the Ericaceae, this assembly is similar to that of Vaccinium macrocarpon at 459 678 bp ( Fajardo et al 2014 ) but considerably smaller than that of the saprophytic Hypopitys monotropa (810 116 bp; Shtratnikova et al 2020 ; also known as Monotropa hypopitys ) or Rhododendron simsii (802 707 bp; Yang et al 2020 ).…”
Section: Resultsmentioning
confidence: 81%
“…While it is possible that genes integrated in the nuclear or mitochondrial genomes (indeed, transfers from the plastid to the nuclear and mitochondrial genome are frequent in plants, see, e.g., Martin and Herrmann, 1998 ; Wang et al, 2007 ) before being lost from the plastome can hypothetically be transferred back, no such cases have been observed up to date. Our recent study of the mitochondrial genome of another mycoheterotropic plant with a highly reduced plastome, Hypopitys monotropa Crantz, showed that while it carries the fragments of plastid genes that are absent in the present-day plastome, none of them retains potentially functional ORFs ( Shtratnikova et al, 2020 ). Also, an investigation of the transcriptomes of three mycoheterotrophic species did not reveal that any genes lost from the plastome were expressed elsewhere ( Schelkunov et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%